Occurrence and economic impact of cystic echinococcosis in cattle slaughtered in the Matabeleland Region, Zimbabwe - Machakwa Jairus; Chivheya Jeff; Chimbo Jeffrey; Sungirai Marvelous (Elsevier, 2023)
Background